2020
DOI: 10.3390/molecules25204692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sonication and Taraxacum Officinale Addition on the Antioxidant and Anti-ACE Activity of Protein Extracts from Sous Vide Beef Marinated with Sour Milk and after In Vitro Digestion

Abstract: The present study assessed the effect of pretreating beef as a raw material for sous vide steak preparation. The pretreatment involved maceration of a batch of meat in sour milk with the simultaneous use of ultrasound (250 or 500 W) as well as the addition of Taraxacum officinale. The biological activity profile of the peptides was assessed in terms of their antioxidant activity and inhibiting activity against angiotensin-converting enzyme (ACE). Changes in the biological activity of peptides under the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…China, United States, and Brazil are the world's top three consumers of beef [1]. Beef is popular among the public and some fitness enthusiasts because of its high protein and low lipid content [2]. It is worth mentioning that studies have shown that the composition of amino acids in beef is very close to the amino acids needed by the human body, which has a significant effect on enhancing human immunity.…”
Section: Introductionmentioning
confidence: 99%
“…China, United States, and Brazil are the world's top three consumers of beef [1]. Beef is popular among the public and some fitness enthusiasts because of its high protein and low lipid content [2]. It is worth mentioning that studies have shown that the composition of amino acids in beef is very close to the amino acids needed by the human body, which has a significant effect on enhancing human immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Kenny et al [27] demonstrated that Taraxacum officinale root extracts can be used as a potential natural preservative to retard oxidative processes in food products. Kęska et al [28] used the combination of ultrasound with dandelion extracts to prepare a functional beef-meat product with enhanced antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al (2015) found that protein digestibility decreased with an increase in core temperature, which could be attributed to protein aggregation [97]. Due to the low temperature of approximately 60-80 °C under a vacuum, the sous vide cooking method can suppress protein aggregation, and the digestion rate can be increased by increasing the total surface area of the protein [98,99]. In an experiment measuring the digestion rate of pork according to the actual cooking temperature, pork heated at a temperature above 100 °C showed a slower digestion rate than pork cooked at a low 2021) reported that with increasing temperature (50, 60, and 70 °C) and time (15 and 30 min), the digestibility of sturgeon myofibrillar protein decreased, whereas the particle size and protein aggregation increased [103].…”
Section: Physical Methods To Improve Protein Digestion 451 Thermal Tr...mentioning
confidence: 99%